The Adequacy of the Term of Reference for the Construction Management (CM) Education and Training from the Perspective of Practitioners in Malaysia - Mustaffa Kamal, Mohd Firdaus; Jing Rui, Tang; Mat Nasir, Nasyairi; Abas, Nor Haslinda; Hanapi, Zaliza; Raja Abdullah, Raja Nazim; Mohd Affandi, Haryanti (Journal of Technical Education and Training, 2020)
The increase in requirement and complexity in managing construction projects has in-part compelled graduates to be highly capable and possessed adequate skills for them to perform well after graduating. To equipped graduates with the required standard, the education curriculum has to be re-design and re-align to the needs of the industry. However, to develop a structured and holistic curriculum, a proper reference framework need to be made available as a term of reference to ensure that the curriculum comprises all the necessary elements to prepare the graduates for the industry. This paper aims to report on the perception of the industry practitioner and stakeholders on the currently available reference framework used as a term of reference for developing the Construction Management education and training program. A qualitative approach using exploratory design has been adopted, which uses an open-ended questionnaire for data collection, drawing insight from experienced construction practitioners and the stakeholders. The questionnaire has been distributed during the Association of Project Managers Malaysia (ACPM) â€˜The Tarikâ€™ session. It has been found that the available reference framework only provides the key knowledge area in Construction Management. It is found that the standards are insufficient and confusing and also not standardized and not integrated. It has consequently created different perceptions of how Construction Management should be practice and thus create a variable in the Construction Management curriculum. It is suggested that a more structured and holistic approach needs to be adapted to provide the ’know-how’ of Construction Management, and a commonly recognized term of reference is needed to be made available to achieve the desired outcome.